Treatment strategies for locally advanced non-small cell lung cancer in elderly patients: Translating scientific evidence into clinical practice. (July 2021) - Bonanno, Laura; Attili, Ilaria; Pavan, Alberto; Sepulcri, Matteo; Pasello, Giulia; Rea, Federico; Guarneri, Valentina; Conte, PierFranco
Graphical abstract: Highlights: Current standard treatments for locally advanced NSCLC. Focus on treatments for locally advanced NSCLC in elderly patients. Main issues for multimodality approach in elderly patients. Abstract: Treatment of locally advanced NSCLC (LA-NSCLC) is focused on multimodal strategy, including chemotherapy and radiotherapy (in combination or as alternative treatments), followed by surgery in selected cases. Recently, durvalumab consolidation after definitive chemo-radiation has shown a meaningful overall survival benefit. However, it is important to note that elderly patients represent a high proportion of NSCLC population and frailty and comorbidities can significantly limit treatment options. Indeed, elderly patients are under-represented in clinical trials and data to drive treatment selection in this category of patients are scanty. Available data, main issues and controversies on multimodal treatment in elderly LA-NSCLC patients will be reviewed in this paper.